PHENETIC ANALYSIS OF GOSSYPIUM SPECIES (MALVACEAE) FROM INDONESIA - Juswara, Lina Susanti (Perhimpunan Biologi Indonesia, 2013)
This research was aimed to revise the species of Gossypium in Indonesia with statistical analysis of morphologicalcharacteristics. Three species of Gossypium were recognized based on phenetic analyses (cluster analysis-UPGMAand ordination-Principle Component Analysis) using 20 morphological characters and 18 samples of Gossypiumarboreum, G. barbadense, and G. hirsutum. Based on these analyses, two varieties were differentiated under G. arboreum(var. arboreum and var. acuminatum). The data set used for the analysis was robust in separating the samplesused in the analysis into discrete groups and cluster analysis-UPGMA and ordination-PCA were powerful tools forthe allocation of those samples into identifiable groups.Keywords: Phenetic analysis, Gossypium, Principal Component Analysis, UPGMA